PTH-012 Preliminary results of a novel temperature controlled endo luminal radio-frequency ablation (elra) electrode for treatment of blocked biliary stents in patients with inoperable pancreaticobiliary cancers. (17th June 2017) - Nayar, M; Oppong, K; Bekkali, N; Leeds, J
Abstract : Introduction: Radiofrequency ablation (RFA) has been used in the treatment of blocked biliary metal stents in patients with pancreaticobiliary (PB) tumours with varying results. Complications have been reported with the commonly used probe. This could be related to lack of temperature control and the inability to establish contact with malignant tissue. We report the preliminary results of a novel temperature controlled probe with better tissue apposition for the treatment of blocked biliary stents in PB tumours. Method: Patients with a confirmed diagnosis of inoperable cancer and a blocked biliary stent were included in this study. Informed consent was obtained for the procedure. ELRA TM RFA electrode (Taewoong Medical) was used for the treatment of these patients (Figure 1). The probe is a bipolar electrode with a temperature sensor which helps with controlled ablation and prevents tissue charring. The catheter is 7Fr in diameter (length=175 cms) with an exposure length of 18 mm. Standard protocol was 10 W at 75 degrees administered for 2 min. The procedure was repeated if stricture resolution was suboptimal. Biliary stent was reinserted if necessary to maintain drainage. Immediate and late adverse events and outcomes at 30 days were recorded. Results: 8 procedures were done on 7 patients (5 males) from April 2016 to January 2017. Aetiology were pancreatic cancer (2); hilar cholangiocarcinoma (2), gall bladder cancer (1), colorectal metastasis (1) and distal cholangiocarcinoma (1). All patients had one prior ERCP procedure. The median length of the stricture was 17 mm (15–25 mm). In 2 patients the procedure was repeated to ensure definitive treatment. One patient had 2 procedures due to a very tight stricture. 5/7 patients required additional stents to ensure optimal drainage. There were no complications and none of the patients have required repeat procedures. Mean follow up period=82.6 days (32 – 225) and 3/7 (43%) patients died due to end stage disease. Conclusion: This is the first reported data on the use of a novel temperature controlled RFA catheter for the treatment of blocked biliary stents in patients with inoperable PB tumours. The device appears safe and effective; however further randomised trials with long term follow up and larger numbers are required. Disclosure of Interest: None Declared